Reinvestigating the phylogeny of Myriapoda with more extensive taxon sampling and novel genetic perspective - Jiajia Wang; Yu Bai; Haifeng Zhao; Ruinan Mu; Yan Dong (PeerJ, 2021)
Background There have been extensive debates on the interrelationships among the four major classes of Myriapoda—Chilopoda, Symphyla, Diplopoda, and Pauropoda. The core controversy is the position of Pauropoda; that is, whether it should be grouped with Symphyla or Diplopoda as a sister group. Two recent phylogenomic studies separately investigated transcriptomic data from 14 and 29 Myriapoda species covering all four groups along with outgroups, and proposed two different topologies of phylogenetic relationships. Methods Building on these studies, we extended the taxon sampling by investigating 39 myriapods and integrating the previously available data with three new transcriptomic datasets generated in this study. Our analyses present the phylogenetic relationships among the four major classes of Myriapoda with a more abundant taxon sampling and provide a new perspective to investigate the above-mentioned question, where visual genes’ identification were conducted. We compared the appearance pattern of genes, grouping them according to their classes and the visual pathways involved. Positive selection was detected for all identified visual genes between every pair of 39 myriapods, and 14 genes showed positive selection among 27 pairs. Results From the results of phylogenomic analyses, we propose that Symphyla is a sister group of Pauropoda. This stance has also received strong support from tree inference and topology tests.